Pengelolaan SDM Pada Kepemimpinan Kepala Sekolah Perempuan Untuk Meningkatkan Mutu Pendidikan Di UPT SDN 20 Baringin - Dini Febriyenti; Jamilus (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This study aimed at describing the leadership strategy of women principal. This research was done in UPT SDN 20 Baringin, Tanah Datar. The approach used in this research was a case study. Results of the study in improving the quality of education in UPT SDN 20 Baringin, Tanah Datar include a good per sonal approach with all stakeholders of the school; planning the school with the greatest extent possible, analyze the challenges, barriers and opportunities in the future; establish good cooperation with all educators, empowering educational effort through cooperation, provide an opportunity to improve educators’ practices, and encourage the involvement of the educators on supporting the programs of the school. These results have implications for teachers maximizing existing facilities and infrastructure to maximize the learning process, and schools already have cultural values ​​such as a culture of politeness in speaking, dressing and all aspects of life.